Physical properties and transmission spectrum of the WASP-74 planetary system from multiband photometry - Mancini, Luigi; Hundertmark, Markus; Küffmeier, Michael (Monthly notices of the Royal Astronomical Society, 2019)
Abstract. We present broad-band photometry of 11 planetary transits of the hot Jupiter WASP-74 b, using three medium-class telescopes and employing the telesco
Gesehen am 31.05.2019